Dry molten globule-like intermediate during the base-induced unfolding of a multidomain protein - Acharya, Nirbhik; Mishra, Prajna; Jha, Santosh Kumar (Physical Chemistry Chemical Physics, 2017)
The nature of the initial structural events during the base-induced unfolding of the native (N) state of proteins is poorly understood. Combining site-specific fluorescence resonance energy transfer, size exclusion chromatography, dynamic fluorescence quenching, red-edge excitation shift and circular dichroism spectroscopy, we show here that an early intermediate during the base-induced unfolding of a multidomain protein, i.e., the B form, has features of a dry molten globule. We show that the N (sic) B transition involves protein expansion and loosening of packing of inter-domain helices near domains I and II without the disruption of intra-domain packing or any change in hydration of the inter-domain region which resembles a molten hydrocarbon. Surprisingly, the disruption of inter-domain packing accounts for 40-45% of the total change in free energy of complete unfolding. Our results show that the disruption of van der Waals packing can be decoupled in different regions of a protein and could occur prior to hydrophobic solvation during base-induced unfolding, challenging the existing notion.

Dry molten globule-like intermediate during the base-induced unfolding of a multidomain protein (vol 19, pg 20307, 2017) - Acharya, Nirbhik; Mishra, Prajna; Jha, Santosh Kumar (Physical Chemistry Chemical Physics, 2019)

Dry molten globule-like intermediates in protein folding, function, and disease - Acharya, Nirbhik; Jha, Santosh Kumar (Journal of Physical Chemistry B, 2022)
The performance of a protein depends on its correct folding to the final functional native form. Hence, understanding the process of protein folding has remained an important field of research for the scientific community for the past five decades. Two important intermediate states, namely, wet molten globule (WMG) and dry molten globule (DMG), have emerged as critical milestones during protein folding-unfolding reactions. While much has been discussed about WMGs as a common unfolding intermediate, the evidence for DMGs has remained elusive owing to their near-native features, which makes them difficult to probe using global structural probes. This Review puts together the available literature and new evidence on DMGs to give a broader perspective on the universality of DMGs and discuss their significance in protein folding, function, and disease.